How do PTAs Address “Competitive Neutrality” between State and Private Owned Enterprises? - Dordi, Claudio (VNU Journal of Science: Social Sciences and Humanities; Vol 32 No 1S, 2016)
States-owned enterprises (SOEs) have for long used as and are likely to remain an important instrument in any government’s toolbox for a variety of economic, public and societal goals. However, the significant extent of state ownership among the world’s top companies raises the issue of its impact on international trade and global competition. We address the question of how multilateral and preferential trade agreements (PTAs) discipline SOEs with a view to guaranteeing the level playing field between such entities and private enterprises, while, at the same time, allowing governments to provide support to SOEs that deal with market failures and provide public goods. The argument is developed in three main parts. The first briefly outlines the reasons why SOEs are disciplined by a number of international legal instruments. The second assesses how WTO agreements deal with the potential trade effects of SOEs and highlights the main shortcomings of the multilateral trade discipline. The third part analyses the chapters on SOEs of the Transpacific Trade Partnership (TTP) and the EU-Vietnam FTA (EUVFTA), which represent, respectively, for the US and the EU, the PTAs endowed with the most advanced provisions on the matter. We will conclude with some concise remarks.